Predicting physical activity and sarcopenia‐related health outcomes in women with rheumatoid arthritis: A test of the self‐determination theory - Chun‐Ja Kim; Hye‐Won Yun; Hee Sun Kang; Ju‐Yang Jung; Elizabeth A Schlenk (Wiley, 2023)
Abstract Aim This study aimed to examine a hypothetical model of physical activity (PA) and health outcomes related to sarcopenia in women with rheumatoid arthritis (RA) based on self‐determination theory. Design Cross‐sectional study. Methods This study included 214 women diagnosed with RA from the outpatient rheumatology department of a university‐affiliated hospital in South Korea. Data were collected from September 2019 to August 2020 through structured questionnaires and anthropometric measurements and analysed using path analysis to test the hypothesized model. The primary health outcomes were perceived health status and sarcopenia‐related health (thigh circumference, handgrip strength and sarcopenia risk). Results The final model's fit indices were adequate. Physical activity was directly affected by motivation for PA, while depression, self‐efficacy for PA, health care provider's autonomy support and basic psychological needs satisfaction indirectly affected PA. Physical activity directly affected perceived health status and thigh circumference, while perceived sarcopenia risk and handgrip strength were directly affected by disease activity and age. Patient or Public Contribution Patients were involved in a questionnaire‐based survey.